Short Communication: Mitochondrial cytochrome b gene analysis reveals lineage history of Indonesian Bubalus bubalis - AKHMAD SUKRI; I GDE ADI SURYAWAN WANGIYANA; HUSNUL JANNAH; GITO HADIPRAYITNO; KHOLIK KHOLIK; FEDERICO DRUDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sukri A, Wangiyana IGAS, Jannah H, Hadiprayitno G, Kholik, Drudi F. 2025. Short Communication: Mitochondrial cytochrome b gene analysis reveals lineage history of Indonesian Bubalus bubalis. Biodiversitas 26: 4654-4661. Swamp buffalo, Bubalus bubalis, is one of the livestock that strongly influences Indonesian social culture. Phylogeography analysis to predict the lineage history of this species is essential for developing this species, especially for breeding purposes. Thus, this study aims to analyze the lineage history and phylogenetic relationship of Indonesian B. bubalis using the cytochrome b gene of mitochondrial DNA. Blood samples of B. bubalis were taken from 7 sampling regions in Indonesia: Aceh (3 sites), Riau (1 site), Blitar (2 sites), Kalimantan (3 sites), Lombok (3 sites), Madiun (2 sites), and Tana Toraja (3 sites). DNA extraction is conducted from the blood sample, followed by PCR (Polymerase Chain Reaction) amplification using forward primer L14841 and reverse primer H155149, followed by sequencing and reference search using MegaBLAST (Basic Local Alignment Search Tool). The phylogenetic relationship, based on Neighbor Joining and Maximum Likelihood trees, shows that Indonesian B. bubalis from the Western Indonesia group (Aceh, Riau, Madiun, and Blitar) has a close relation with B. bubalis from India, Bangladesh, Pakistan, and Nepal. Meanwhile, Indonesian B. bubalis from Central Indonesia (Kalimantan, Lombok, and Tator) has a close relation with B. bubalis from China, Japan, Laos, Vietnam and Thailand. It could be concluded that Indonesian B. bubalis exhibit two distinct maternal lineages, indicating dual domestication routes: the South Asia lineage with a domestication center in India and spread out to Western Indonesia (Aceh, Riau, Blitar) and the East Asia lineage with a domestication center in China and spread out to Central Indonesia (Kalimantan and Lombok). Lineage analysis of Indonesian B. bubalis can have a significant impact on biodiversity, enriching worldwide genetic mapping and providing conservation data for breeding this species.